Modified nano calcium carbonate, polyolefin plastic pipe and preparation method thereof

By using modified nano calcium carbonate and hyperbranched polyester as reinforcement agents in plastic tubes, the problem of prone to deformation or rupture in high-pressure environments is solved, and the strength and pressure resistance of the plastic tubes are significantly improved.

CN119708630APending Publication Date: 2025-03-28JIANGSU NOBEL PLASTICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023105.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional plastic pipes are prone to deform or breaking in high-pressure environments, resulting in a shorter service life.

Method used

Modified nano calcium carbonate and hyperbranched polyester are used as reinforcers to form a physicochemical adsorption layer on the surface of nano calcium carbonate particles to prevent particles from agglomeration, and the dispersion of nano calcium carbonate is improved through the special structure of hyperbranched polyester, thereby enhancing the strength of the plastic tube.

Benefits of technology

It significantly improves the strength and pressure resistance of plastic pipes, extends service life, and maintains high strength at high temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to modified nano calcium carbonate, a polyolefin plastic pipe and a preparation method thereof, and relates to the technical field of plastic pipes. The polyolefin plastic pipe is prepared by modifying nano calcium carbonate, the polyolefin plastic pipe is prepared from the following raw materials in parts by mass: 80-90 parts of polyolefin, 10-18 parts of dioctyl phthalate, 2-4 parts of calcium stearate, 2-4 parts of 2, 6-di-tert-butylphenol and 25-30 parts of a reinforcing agent, and the reinforcing agent comprises modified nano calcium carbonate. The plastic pipe has the effects of improving the strength of the plastic pipe and prolonging the service life of the plastic pipe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of plastic pipes, and in particular to a modified nano calcium carbonate, polyolefin plastic pipe and a preparation method thereof. Background Art

[0002] Plastic pipes are generally made of synthetic resin, that is, polyester, with stabilizers, lubricants, plasticizers, etc., and are extruded in a pipe making machine by the "plastic" method. Plastic pipes have the advantages of light weight, high strength, simple manufacturing method, low economic cost, convenient processing and use, corrosion resistance, and long life. They are gradually replacing metal, cement and other pipes and have become the main application pipes in urban construction, rural water network laying, electrical transmission and other fields.

[0003] However, with the continuous expansion of application scenarios, such as under high-pressure environments, traditional plastic pipes are prone to deformation or even rupture, thereby reducing the service life of plastic pipes. Summary of the invention

[0004] In order to improve the strength of plastic pipes and extend the service life of plastic pipes, the present application provides a modified nano calcium carbonate, a polyolefin plastic pipe and a preparation method thereof.

[0005] In the first aspect, the present application provides a modified nano calcium carbonate, which adopts the following technical solution: The modified preparation method of modified nano calcium carbonate comprises the following steps: S1, after mixing citric acid, polyethylene glycol and a catalyst, heating and stirring, reacting under nitrogen protection at normal pressure, and then reacting under reduced pressure to complete the first stage of the reaction, further adding citric acid in the second stage, continuing the normal pressure and reduced pressure reaction as in the first stage, to obtain a product, then adding the product to acetone, and then adding n-hexane to precipitate it, and then filtering and drying to obtain a hyperbranched polyester; S2. Add nano calcium carbonate and hyperbranched polyester into N,N-dimethylformamide, heat in a water bath, and then stir. After the reaction is completed, reduce pressure, filter, dry, grind, and sieve to obtain modified nano calcium carbonate.

[0006] By adopting the above technical solution, since the nano calcium carbonate particles are easy to agglomerate, it is easy to cause poor bonding between the nano calcium carbonate and the plastic pipe matrix, thereby affecting the strength of the plastic pipe.

[0007] Therefore, a hyperbranched polyester with carboxyl terminal groups is generated by using citric acid and polyethylene glycol, and nano-calcium carbonate and the hyperbranched polyester are dispersed in N,N-dimethylformamide, so that the hyperbranched polyester molecules are grafted and adsorbed on the surface of the nano-calcium carbonate particles. The hyperbranched polyester can form a physical and chemical adsorption layer with the surface of the nano-calcium carbonate particles to prevent the nano-calcium carbonate particles from agglomerating. The special hyperbranched structure also makes the nano-calcium carbonate have good dispersibility, enhances the bonding force between the nano-calcium carbonate and the plastic pipe matrix, and thus improves the strength of the plastic pipe.

[0008] Preferably, the mass ratio of the nano-calcium carbonate to the hyperbranched polyester is 1:(0.05-0.15).

[0009] By adopting the above technical solution, the mass ratio of nano-calcium carbonate to hyperbranched polyester is controlled within the above range, which can effectively improve the dispersibility of nano-calcium carbonate.

[0010] On the other hand, the present application provides a polyolefin plastic pipe, comprising the following raw materials in parts by weight: 80-90 parts of polyolefin, 10-18 parts of dioctyl phthalate, 2-4 parts of calcium stearate, 2-4 parts of 2,6-di-tert-butylphenol, and 25-30 parts of a reinforcing agent; The reinforcing agent includes the modified nano calcium carbonate.

[0011] By adopting the above technical solution, the strength of the plastic pipe can be effectively improved by adding modified nano calcium carbonate as a reinforcing agent to the raw material of the plastic pipe. The modified nano calcium carbonate has the effect of strengthening and toughening, effectively improving the strength of the plastic pipe, and then when the plastic pipe is under high pressure, the possibility of deformation of the plastic pipe is reduced, and the service life of the plastic pipe is effectively extended.

[0012] Preferably, the reinforcing agent further comprises modified talc powder, and the mass ratio of the modified nano-calcium carbonate to the modified talc powder is 1:(4.1-4.5).

[0013] By adopting the above technical solution, the modified talcum powder is a layered silicate mineral. The addition of the modified talcum powder can significantly improve the tensile strength of the plastic pipe and give it good impact resistance, thereby improving the strength of the plastic pipe.

[0014] Moreover, the hydroxyl groups in the modified talc can form hydrogen bonds with the hydroxyl groups and carboxyl groups in the nano-calcium carbonate grafted with the hyperbranched polyester, thereby enhancing the bonding force between the modified talc and the polyolefin and the dispersion effect of the modified talc by means of the excellent dispersibility and compatibility of the nano-calcium carbonate grafted with the hyperbranched polyester, and playing a positive role in improving the strength of the plastic pipe.

[0015] In addition, when modified talc and modified nano-calcium carbonate are added to plastic pipes as reinforcing agents, the modified talc with a lamellar structure plays a better reinforcing role, and the granular nano-calcium carbonate is dispersed in the plastic pipe matrix, which can hinder the propagation of cracks. Based on the above-mentioned molecular forces, the two different forms of reinforcing agents are arranged in a uniformly spaced manner in the pipe matrix, which is conducive to improving the strength. Compared with unmodified nano-calcium carbonate, the same amount of addition greatly improves the strength of the plastic pipe.

[0016] Nano-calcium carbonate and hyperbranched polyester are combined through chemical bonds, which have stronger binding force, achieving a more lasting dispersion effect of nano-calcium carbonate and maintaining long-lasting high strength of the pipe. The modified talcum powder and the hyperbranched polyester on the surface of the modified nano-calcium carbonate are combined with hydrogen bonds. On the one hand, the dispersion of the modified talcum powder is improved. On the other hand, when the plastic pipe is subjected to external force, the modified talcum powder can flexibly achieve system-enhanced filling, better release stress, prevent cracks, and increase the service life of the pipe.

[0017] In addition, modified talcum powder has excellent heat resistance, so the addition of modified talcum powder can greatly improve the heat resistance of plastic pipes, which is more conducive to the use of plastic pipes at high temperatures.

[0018] Preferably, the modified preparation method of the modified talc powder comprises the following steps: After adjusting the pH of the ethanol aqueous solution to 4 with glacial acetic acid, a silane coupling agent is added. After sufficient reaction, talcum powder is added, heated and stirred, and then washed, filtered, dried and ground to obtain modified talcum powder.

[0019] By adopting the above technical scheme, after the surface of talcum powder is modified by silane coupling agent, the hydroxyl groups on its surface react with the hydroxyl groups after hydrolysis of the alkoxy groups of the silane coupling agent, thereby firmly fixing the silane coupling agent on the surface of talcum powder, so that the surface of talcum powder is covered with a layer of organic network film, thereby improving the interface compatibility between talcum powder and polyolefin, enhancing the steric hindrance between talcum powder particles, reducing agglomeration, and thus improving the strength of the plastic pipe.

[0020] At this time, the functional group at the other end of the silane coupling agent strengthens the hydrogen bonding effect with the terminal carboxyl group of the hyperbranched polyester, effectively improving the binding force between talc and nano-calcium carbonate.

[0021] In addition, due to the improved dispersibility of talc in the plastic pipe matrix, the orientation during the blending process is better, forming a continuous rigid skeleton, so that the polyolefin molecular segments between the skeleton are fixed, limiting the movement of the molecular chains, increasing the heat deformation temperature, and thus improving the high temperature resistance of the plastic pipe.

[0022] Preferably, the mass ratio of the talc powder to the silane coupling agent is 1:(0.02-0.04).

[0023] By adopting the above technical solution, the mass ratio of talcum powder to silane coupling agent is controlled within the above range, which can effectively improve the dispersibility of talcum powder.

[0024] Preferably, the silane coupling agent is an aminosilane coupling agent, and the aminosilane coupling agent is KH-602.

[0025] Preferably, the raw material also includes 9-13 parts of ethylene-octene copolymer.

[0026] By adopting the above technical solution, since the ethylene-octene copolymer has good flexibility, the strength of the plastic pipe can be improved by adding the ethylene-octene copolymer to the plastic pipe.

[0027] After talc is treated with silane coupling agent, there is good compatibility and interface bonding between talc and ethylene-octene copolymer. When the plastic pipe is subjected to external impact, talc can serve as a stress center and prevent crack propagation by deforming the ethylene-octene copolymer around the talc, thereby further improving the reinforcement effect on the plastic pipe.

[0028] In addition, the addition of ethylene-octene copolymer can optimize the crystallinity and grain size of the plastic pipe, thereby improving the thermal stability of the material, and the talc modified with silane coupling agent can promote the crystallization of the plastic pipe material, further improving the heat resistance of the plastic pipe.

[0029] On the other hand, the present application provides a method for preparing a polyolefin plastic pipe, which adopts the following technical solution: A method for preparing a polyolefin plastic pipe comprises the following steps: The polyolefin, dioctyl phthalate, calcium stearate, 2,6-di-tert-butylphenol and reinforcing agent are mixed and stirred evenly, and then the plastic pipe is obtained by extrusion and pipe making in sequence.

[0030] In summary, the present application includes at least one of the following beneficial technical effects: 1. Modified nano calcium carbonate has the effect of strengthening and toughening, which effectively improves the strength of plastic pipes. When the plastic pipes are under high pressure, the possibility of deformation of the plastic pipes is reduced, effectively extending the service life of the plastic pipes.

[0031] 2. Modified talcum powder can significantly improve the tensile strength of plastic pipes and give them good impact resistance. The hydroxyl groups in the modified talcum powder can form hydrogen bonds with the hydroxyl and carboxyl groups in the modified nano-calcium carbonate, thereby improving the bonding force between the modified talcum powder and polyolefins, which has a positive effect on improving the strength of plastic pipes.

[0032] 3. When modified talcum powder and hyperbranched polyester modified nano-calcium carbonate are added to plastic pipes as reinforcing agents, the modified talcum powder with a lamellar structure plays a better reinforcing role, and the granular nano-calcium carbonate is dispersed in the plastic pipe matrix, which can hinder the expansion of cracks. Thus, there is a synergistic effect between the two, which has a positive effect on improving the strength of the plastic pipe. DETAILED DESCRIPTION

[0033] The present application discloses a modified nano calcium carbonate, a polyolefin plastic tube and a preparation method thereof, and the present application is further described in detail in combination with the embodiments and comparative examples. The raw materials involved in the present application can be obtained from the market, wherein the polyolefin model is K9928H, purchased from PetroChina Dushanzi Petrochemical Company; the ethylene-octene copolymer model is 8150, purchased from Dow Chemical Company; polyethylene glycol 6000 is purchased from Sinopharm Chemical Reagent Co., Ltd.; aminosilane coupling agent KH-602 (CAS number: 3069-29-2) is purchased from Guangzhou Longkai Chemical Co., Ltd.

[0034] Example 1 The plastic pipe includes the following raw materials in mass: 85 g of polyolefin, 14 g of dioctyl phthalate, 3 g of calcium stearate, 3 g of 2,6-di-tert-butylphenol, and 28 g of a reinforcing agent.

[0035] The reinforcing agent includes nano calcium carbonate.

[0036] The method for preparing a plastic pipe comprises the following steps: Polyolefin, dioctyl phthalate, calcium stearate, 2,6-di-tert-butylphenol and reinforcing agent are mixed and stirred evenly, then extruded through a twin-screw extruder, and finally added to a pipe making machine to make a plastic pipe, wherein the four zone temperatures of the twin-screw extruder are 160°C, 175°C, 185°C and 170°C respectively, and the screw speed is 15r / min.

[0037] Example 2 The plastic pipe includes the following raw materials in mass: 85 g of polyolefin, 14 g of dioctyl phthalate, 3 g of calcium stearate, 3 g of 2,6-di-tert-butylphenol, and 28 g of a reinforcing agent.

[0038] The reinforcing agent comprises nano calcium carbonate and talcum powder, and the mass ratio of the nano calcium carbonate to the talcum powder is 1:4.3.

[0039] The preparation method of the enhancer comprises the following steps: The nano calcium carbonate and talcum powder are mixed and stirred evenly to prepare a reinforcing agent.

[0040] The method for preparing a plastic pipe comprises the following steps: Polyolefin, dioctyl phthalate, calcium stearate, 2,6-di-tert-butylphenol and reinforcing agent are mixed and stirred evenly, then extruded through a twin-screw extruder, and finally added to a pipe making machine to make a plastic pipe, wherein the four zone temperatures of the twin-screw extruder are 160°C, 175°C, 185°C and 170°C respectively, and the screw speed is 15r / min.

[0041] Example 3 The plastic pipe includes the following raw materials in mass: 80g of polyolefin, 10g of dioctyl phthalate, 2g of calcium stearate, 2g of 2,6-di-tert-butylphenol, and 25g of a reinforcing agent.

[0042] The reinforcing agent comprises nano calcium carbonate and talcum powder, and the mass ratio of the nano calcium carbonate to the talcum powder is 1:4.1.

[0043] The preparation method of the enhancer comprises the following steps: The nano calcium carbonate and talcum powder are mixed and stirred evenly to prepare a reinforcing agent.

[0044] The method for preparing a plastic pipe comprises the following steps: Polyolefin, dioctyl phthalate, calcium stearate, 2,6-di-tert-butylphenol and reinforcing agent are mixed and stirred evenly, then extruded through a twin-screw extruder, and finally added to a pipe making machine to make a plastic pipe, wherein the four zone temperatures of the twin-screw extruder are 160°C, 175°C, 185°C and 170°C respectively, and the screw speed is 15r / min.

[0045] Example 4 The plastic pipe includes the following raw materials in mass: 90 g of polyolefin, 18 g of dioctyl phthalate, 4 g of calcium stearate, 4 g of 2,6-di-tert-butylphenol, and 30 g of a reinforcing agent.

[0046] The reinforcing agent comprises nano calcium carbonate and talcum powder, and the mass ratio of the nano calcium carbonate to the talcum powder is 1:4.5.

[0047] The preparation method of the enhancer comprises the following steps: The nano calcium carbonate and talcum powder are mixed and stirred evenly to prepare a reinforcing agent.

[0048] The method for preparing a plastic pipe comprises the following steps: Polyolefin, dioctyl phthalate, calcium stearate, 2,6-di-tert-butylphenol and reinforcing agent are mixed and stirred evenly, then extruded through a twin-screw extruder, and finally added to a pipe making machine to make a plastic pipe, wherein the four zone temperatures of the twin-screw extruder are 160°C, 175°C, 185°C and 170°C respectively, and the screw speed is 15r / min.

[0049] Example 5 The difference between Example 5 and Example 2 is that the mass ratio of nano-calcium carbonate to talcum powder is 1:3.9.

[0050] Example 6 The difference between Example 6 and Example 2 is that the mass ratio of nano-calcium carbonate to talcum powder is 1:4.7.

[0051] Example 7 The difference between Example 7 and Example 2 is that the nano calcium carbonate is prepared by modification, and the modification preparation method of the nano calcium carbonate comprises the following steps: S1. After mixing 11g of citric acid, 9g of polyethylene glycol and 0.2g of catalyst, heat the mixture in an oil bath to 160°C, use mechanical stirring, react at normal pressure for 3h under nitrogen protection, and then use a rotary vane vacuum pump to reduce pressure for 1h, and the reduced pressure reaction pressure is about 0.6kPa to complete the first stage of the reaction; in the second stage, further add 32g of citric acid, continue to react at normal pressure for 3h, and reduce pressure for 3h as in the first stage to obtain a product, dissolve the product in 200g of acetone, add 46g of n-hexane to precipitate it, and leave the catalyst in the mixed solvent. After filtering and drying, a hyperbranched polyester is obtained; S2. Add 30g of nano calcium carbonate and 1.5g of hyperbranched polyester to 200g of N,N-dimethylformamide, heat to 75°C in a water bath, stir and react for 1h at a constant stirring speed (500r / min), and then filter under reduced pressure. Place the filter cake in a forced draft drying oven at 100°C and dry it for 3h. Then grind it and sieve it through a 200-mesh standard sieve to obtain modified nano calcium carbonate.

[0052] The molecular weight of polyethylene glycol is 6000, and the catalyst is p-toluenesulfonic acid.

[0053] Example 8 The difference between Example 8 and Example 2 is that the nano calcium carbonate is prepared by modification, and the modification preparation method of the nano calcium carbonate comprises the following steps: S1. After mixing 11g of citric acid, 9g of polyethylene glycol and 0.2g of catalyst, heat the mixture in an oil bath to 160°C, use mechanical stirring, react at normal pressure for 3h under nitrogen protection, and then use a rotary vane vacuum pump to reduce pressure for 1h, and the reduced pressure reaction pressure is about 0.6kPa to complete the first stage of the reaction; in the second stage, further add 32g of citric acid, continue to react at normal pressure for 3h, and reduce pressure for 3h as in the first stage to obtain a product, dissolve the product in 200g of acetone, add 46g of n-hexane to precipitate it, and leave the catalyst in the mixed solvent. After filtering and drying, a hyperbranched polyester is obtained; S2. Add 30g of nano calcium carbonate and 4.5g of hyperbranched polyester to 200g of N,N-dimethylformamide, heat to 75°C in a water bath, stir and react for 1h at a constant stirring speed (500r / min), and then filter under reduced pressure. Place the filter cake in a forced draft drying oven at 100°C and dry it for 3h. Then grind it and sieve it through a 200-mesh standard sieve to obtain modified nano calcium carbonate.

[0054] The molecular weight of polyethylene glycol is 6000, and the catalyst is p-toluenesulfonic acid.

[0055] Example 9 The difference between Example 9 and Example 2 is that the nano calcium carbonate is prepared by modification, and the modification preparation method of the nano calcium carbonate comprises the following steps: S1. After mixing 11g of citric acid, 9g of polyethylene glycol and 0.2g of catalyst, heat the mixture in an oil bath to 160°C, use mechanical stirring, react at normal pressure for 3h under nitrogen protection, and then use a rotary vane vacuum pump to reduce pressure for 1h, and the reduced pressure reaction pressure is about 0.6kPa to complete the first stage of the reaction; in the second stage, further add 32g of citric acid, continue to react at normal pressure for 3h, and reduce pressure for 3h as in the first stage to obtain a product, dissolve the product in 200g of acetone, add 46g of n-hexane to precipitate it, and leave the catalyst in the mixed solvent. After filtering and drying, a hyperbranched polyester is obtained; S2. Add 30g of nano calcium carbonate and 3g of hyperbranched polyester to 200g of N,N-dimethylformamide, heat to 75°C in a water bath, stir and react for 1h at a constant stirring speed (500r / min), and then filter under reduced pressure. Place the filter cake in a forced draft drying oven at 100°C and dry it for 3h. Then grind it and sieve it through a 200-mesh standard sieve to obtain modified nano calcium carbonate.

[0056] The molecular weight of polyethylene glycol is 6000, and the catalyst is p-toluenesulfonic acid.

[0057] Example 10 The difference between Example 10 and Example 9 is that the mass ratio of nano-calcium carbonate to hyperbranched polyester is 1:0.01.

[0058] Embodiment 11 The difference between Example 11 and Example 9 is that the mass ratio of nano-calcium carbonate to hyperbranched polyester is 1:0.19.

[0059] Example 12 The difference between Example 12 and Example 9 is that: after adjusting the pH of 200g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 90%) to 4 with glacial acetic acid, 0.2g of silane coupling agent is added, and the mixture is allowed to react at 25°C for 10h, and then 10g of talcum powder is added, and the mixture is stirred and reacted at 70°C for 4h. Finally, the mixture is fully washed with acetone, filtered, dried, and ground to obtain modified talcum powder.

[0060] The silane coupling agent is an aminosilane coupling agent, and the aminosilane coupling agent is KH-602.

[0061] Embodiment 13 The difference between Example 13 and Example 9 is that: after adjusting the pH of 200g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 90%) to 4 with glacial acetic acid, 0.4g of silane coupling agent is added, and the mixture is allowed to react at 25°C for 10h, and then 10g of talcum powder is added, and the mixture is stirred and reacted at 70°C for 4h. Finally, the mixture is fully washed with acetone, filtered, dried, and ground to obtain modified talcum powder.

[0062] The silane coupling agent is an aminosilane coupling agent, and the aminosilane coupling agent is KH-602.

[0063] Embodiment 14 The difference between Example 14 and Example 9 is that: after adjusting the pH of 200g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 90%) to 4 with glacial acetic acid, 0.3g of silane coupling agent is added, and the mixture is allowed to react at 25°C for 10h, and then 10g of talcum powder is added, and the mixture is stirred and reacted at 70°C for 4h. Finally, the mixture is fully washed with acetone, filtered, dried, and ground to obtain modified talcum powder.

[0064] The silane coupling agent is an aminosilane coupling agent, and the aminosilane coupling agent is KH-602.

[0065] Embodiment 15 The difference between Example 15 and Example 14 is that the mass ratio of talcum powder to aminosilane coupling agent is 1:0.01.

[0066] Example 16 The difference between Example 16 and Example 14 is that the mass ratio of talc powder to aminosilane coupling agent is 1:0.05.

[0067] Embodiment 17 The difference between Example 17 and Example 14 is that the raw material further includes 9 g of ethylene-octene copolymer.

[0068] That is, the plastic pipe includes the following raw materials: 85g of polyolefin, 14g of dioctyl phthalate, 3g of calcium stearate, 3g of 2,6-di-tert-butylphenol, 28g of reinforcing agent, and 9g of ethylene-octene copolymer.

[0069] The reinforcing agent comprises nano calcium carbonate and talcum powder, and the mass ratio of the nano calcium carbonate to the talcum powder is 1:4.3.

[0070] The preparation method of the enhancer comprises the following steps: The nano calcium carbonate and talcum powder are mixed and stirred evenly to prepare a reinforcing agent.

[0071] The method for preparing a plastic pipe comprises the following steps: Polyolefin, dioctyl phthalate, calcium stearate, 2,6-di-tert-butylphenol, reinforcing agent, and ethylene-octene copolymer are mixed and stirred evenly, then extruded through a twin-screw extruder, and finally added to a pipe making machine to make a plastic pipe, wherein the four zone temperatures of the twin-screw extruder are 160°C, 175°C, 185°C and 170°C respectively, and the screw speed is 15r / min.

[0072] Embodiment 18 The difference between Example 18 and Example 17 is that the raw material further includes 13 g of ethylene-octene copolymer.

[0073] Embodiment 19 The difference between Example 19 and Example 17 is that the raw material further includes 11 g of ethylene-octene copolymer.

[0074] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the reinforcing agent is talcum powder.

[0075] Comparative Example 2 The difference between Comparative Example 2 and Example 14 is that the silane coupling agent is a methylsilane coupling agent, and the methylsilane coupling agent is methyltriethoxysilane.

[0076] Performance testing: The plastic tubes prepared in Examples 1-19 and Comparative Examples 1-2 were cut into a size of 10 mm×10 mm and clamped with two stainless steel clamps to keep the size of the measured material at 2 mm×10 mm. All mechanical property tests were carried out at room temperature.

[0077] (1) Tensile properties: Tested in accordance with GB / T1040.2-2006 Determination of tensile properties of plastics, with a tensile rate of 10 mm / min, and the test results are recorded in Table 1.

[0078] (2) Impact strength: Test according to GB / T1843-2008 Determination of impact strength of plastic cantilever beam, and record the test results in Table 1.

[0079] Table 1 sample Tensile strength / MPa <![CDATA[Notched impact strength / kJ / m 2 > Example 1 25.3 52.7 Example 2 28.7 56.2 Example 3 28.5 55.9 Example 4 28.4 56.1 Example 5 28.0 55.4 Example 6 27.9 55.5 Example 7 31.4 59.2 Example 8 31.4 59.0 Example 9 31.6 59.3 Example 10 30.9 58.5 Embodiment 11 31.1 58.7 Example 12 34.5 62.0 Embodiment 13 34.6 62.1 Embodiment 14 34.8 62.2 Embodiment 15 34.0 61.5 Example 16 34.0 61.4 Embodiment 17 37.1 65.3 Embodiment 18 37.2 65.3 Embodiment 19 37.4 65.5 Comparative Example 1 25.5 52.6 Comparative Example 2 32.8 60.5 Data Analysis: Specifically combining the test results of Example 2 and Example 1, the strength of Example 2 is higher than that of Example 1. The analysis is as follows: the difference between Example 2 and Example 1 is that the reinforcing agent contains talcum powder in addition to nano-calcium carbonate. The synergistic effect of nano-calcium carbonate and talcum powder added to the plastic pipe has a positive effect on improving the strength of the plastic pipe, thereby improving the strength of the plastic pipe.

[0080] Specifically combining the test results of Example 9 and Example 2, the strength of Example 9 is higher than that of Example 2. The analysis is as follows: the difference between Example 9 and Example 2 is that the hyperbranched polyester modifies the nano-calcium carbonate, effectively improving the dispersibility of the nano-calcium carbonate, thereby improving the positive effect of adding nano-calcium carbonate to the plastic pipe on the strength of the plastic pipe.

[0081] Specifically combining the test results of Example 14 and Example 9, the strength of Example 14 is higher than that of Example 9. The analysis is as follows: the difference between Example 14 and Example 9 is that the aminosilane coupling agent is used to modify the talc powder, which not only improves the dispersibility of the talc powder, but also improves the bonding force between the talc powder and the modified nano-calcium carbonate, thereby improving the strength of the plastic pipe.

[0082] Specifically combining the test results of Example 19 and Example 14, the strength of Example 19 is higher than that of Example 14. The analysis is as follows: the difference between Example 19 and Example 14 is that the plastic pipe raw material also contains ethylene-octene copolymer. On the one hand, the ethylene-octene copolymer has good flexibility. On the other hand, there is good compatibility and interface bonding force between the ethylene-octene copolymer and the modified talc, which has a good reinforcement effect on the plastic pipe.

[0083] Specifically combining the test results of Example 2 and Comparative Example 1, it can be seen that the strength of Example 2 is higher than that of Comparative Example 1. The analysis is as follows: the difference between Example 2 and Comparative Example 1 is that the reinforcing agent contains nano-calcium carbonate in addition to talcum powder. The synergistic effect of nano-calcium carbonate and talcum powder added together to the plastic pipe has a positive effect on improving the strength of the plastic pipe, thereby improving the strength of the plastic pipe.

[0084] Specifically combining the test results of Example 14 and Comparative Example 2, it seems that the strength of Example 14 is higher than that of Comparative Example 2. The analysis is as follows: the difference between Example 14 and Comparative Example 2 is that the silane coupling agent is aminosilane coupling agent KH-602, and the bonding force between talcum powder and nano-calcium carbonate is effectively improved through the bonding force between the aminosilane coupling agent and the hyperbranched polyester, thereby having a better reinforcement effect on the plastic pipe.

[0085] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A modified nano calcium carbonate, characterized in that: The modified preparation method of the modified nano calcium carbonate comprises the following steps: S1, after mixing citric acid, polyethylene glycol and a catalyst, heating and stirring, reacting under nitrogen protection at normal pressure, and then reacting under reduced pressure to complete the first stage of the reaction, further adding citric acid in the second stage, continuing the normal pressure and reduced pressure reaction as in the first stage, to obtain a product, then adding the product to acetone, and then adding n-hexane to precipitate it, and then filtering and drying to obtain a hyperbranched polyester; S2, adding nano calcium carbonate and hyperbranched polyester to N, N-dimethylformamide, heating in a water bath, and stirring, and after the reaction is completed, reducing pressure, filtering, drying, grinding, and screening to obtain modified nano calcium carbonate; The mass ratio of the nano calcium carbonate to the hyperbranched polyester is 1:(0.05-0.15).

2. A polyolefin plastic pipe, characterized in that: The raw materials include the following parts by weight: 80-90 parts of polyolefin, 10-18 parts of dioctyl phthalate, 2-4 parts of calcium stearate, 2-4 parts of 2,6-di-tert-butylphenol, and 25-30 parts of reinforcing agent; The reinforcing agent comprises the modified nano calcium carbonate as claimed in claim 1.

3. A polyolefin plastic pipe according to claim 2, characterized in that: The reinforcing agent also includes modified talcum powder, and the mass ratio of the modified nano calcium carbonate to the modified talcum powder is 1: (4.1-4.5).

4. A polyolefin plastic pipe according to claim 3, characterized in that: The modified preparation method of the modified talcum powder comprises the following steps: After adjusting the pH of the ethanol aqueous solution to 4 with glacial acetic acid, a silane coupling agent is added. After sufficient reaction, talcum powder is added, heated and stirred, and then washed, filtered, dried and ground to obtain modified talcum powder.

5. A polyolefin plastic pipe according to claim 4, characterized in that: The mass ratio of the talc powder to the silane coupling agent is 1:(0.02-0.04).

6. A polyolefin plastic pipe according to claim 4, characterized in that: The silane coupling agent is an aminosilane coupling agent, and the aminosilane coupling agent is KH-602.

7. A polyolefin plastic pipe according to claim 4, characterized in that: The raw material also includes 9-13 parts of ethylene-octene copolymer.

8. A method for preparing a polyolefin plastic pipe as claimed in claim 2, characterized in that: The steps include: The polyolefin, dioctyl phthalate, calcium stearate, 2,6-di-tert-butylphenol and reinforcing agent are mixed, stirred evenly, and then extruded and piped in sequence to obtain a plastic pipe.